negosiasi dalam Tanah untuk Pendirian Pabrik Semen Gresik Kabupaten Rembang - dhimas danti rinandyta; wiwik widayati; turtiantoro . (Journal of Politic and Government Studies, 2014)
Semen Gresik (SG) plans plant establishment which will be established in the District Gunem Rembang already starting to sound since 2010. Plan the location of the factory of PT Semen Gresik is located in the village of Pasucen, village and village Tegaldowen Timbrangan Suntri Village, District Gunem, Rembang. This cement plant requires an area of 900 hectares in the district and Bulu.Lahan Gunem the area needed for the procurement of raw material limestone (520 acres), clay (240 acres), factory (105 acres), road mines (15 acres), and way of production (20 acres). The land for the plant and the procurement of raw materials will be focused on the village of Pasucen, Tegaldowo, Kajar, Timbrangan, and Suntri in District Gunem. Residents of communities affected by the development are not concerned with the construction of the cement plant. For land compensation has also been declared settled by agreement between the parties with citizens that Semen Gresik land affected by construction of the plant. Harapanya for the existence of the plant to improve their economy. From these results, it appears that citizens will dibangunya happy with this cement plant. Now the task for the government to monitor, supervise that the existence of this plant does not bring harm to the people around the project. And can provide increased revenue for the District of Apex and the villages around the project of course. Keywords: Negotiation, indemnity Land, Land Acquistion